2020
DOI: 10.1101/2020.09.15.297549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DWV infection and replication at the early stagein vitrousing honey bee pupal cells

Abstract: Deformed wing virus (DWV) has been best characterized among honey bee viruses; however, very little is known about the mechanisms of viral infection and replication due to the lack of honey bee cell lines. To resolve this problem, we established in vitro system to reconstitute DWV binding and entry to the host cell followed by translation of the genome RNA and the polyprotein processing with honey bee pupal cells. Using this system, P-domain of VP1 was found to be essential for DWV infection/replication but no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The head was sagittally dissected to approximately half and each tissue was suspended in 100 μL of Grace medium containing 10% FBS and antibiotics (penicillin and streptomycin) with or without DWV (9.4 × 10 8 copy) in 24-well plate at 33°C for 1 h. Fresh culture medium (400 μL) was then added and incubated at 33°C for 16 h. DWV was pre-incubated with either anti-VP1 P-domain ( Wu et al, 2020a ) or anti-VP1 (524–750) antibody at the indicated amount of protein for 30 min, and then added to the pupal head tissue for infection as above. The dissected pupal head tissue was pre-incubated with either purified VP1 P-domain protein ( Wu et al, 2020a ) or BSA at the indicated amount of protein in Grace culture medium at room temperature for 1 h. DWV was then added for infection as above. Rupintrivir, Quercetin, or DMSO was added to the pupal head tissue at the indicated concentration together with DWV as above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The head was sagittally dissected to approximately half and each tissue was suspended in 100 μL of Grace medium containing 10% FBS and antibiotics (penicillin and streptomycin) with or without DWV (9.4 × 10 8 copy) in 24-well plate at 33°C for 1 h. Fresh culture medium (400 μL) was then added and incubated at 33°C for 16 h. DWV was pre-incubated with either anti-VP1 P-domain ( Wu et al, 2020a ) or anti-VP1 (524–750) antibody at the indicated amount of protein for 30 min, and then added to the pupal head tissue for infection as above. The dissected pupal head tissue was pre-incubated with either purified VP1 P-domain protein ( Wu et al, 2020a ) or BSA at the indicated amount of protein in Grace culture medium at room temperature for 1 h. DWV was then added for infection as above. Rupintrivir, Quercetin, or DMSO was added to the pupal head tissue at the indicated concentration together with DWV as above.…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation, the supernatants were applied to 10% SDS-PAGE and the proteins were transferred to a nitrocellulose membrane (Pall ® Life Sciences). The membrane was then blocked with PBST (PBS with 0.1% Tween-20) containing 5% BSA at room temperature for 1 h followed by incubating with 1,000-fold diluted anti-RdRP antibody ( Wu et al, 2020a ) at 4°C overnight. The membrane was washed three times with PBST (5 min each), and then incubated with 10,000-fold diluted IRDye ® 680RD donkey anti-rabbit IgG (H+L) (LI-COR Biosciences) in PBST containing 5% skim milk at room temperature for 1.5 h. The membrane was washed as above, and then visualized using Odyssey Imaging System (LI-COR Biosciences).…”
Section: Methodsmentioning
confidence: 99%